Construction of multifunctional heterocycles bearing aza-quaternary carbons by titanocene-catalyzed umpolung reactions. Issue 12 (22nd March 2019) - Cheng, Jiang-Tao; Zheng, Xiao; Huang, Pei-Qiang
Abstract: The combined application of Grignard/Reformatsky addition and the titanocene-catalyzed umpolung α-amino carbon-carbon bond formations provided a flexible and versatile protocol for preparation of multifunctional pyrrolidinones/piperidinones/ N -Boc-piperidines bearing aza-quaternary carbons (AQC) from cyclic imides and analogues. Based on these multifunctional single-ring motifs, several advanced AQC-bearing heterocycles, such as AQC-possessing indolizidines and 1-azaspirocycles, have been constructed efficiently. Graphical abstract: Image 1